Fodor's modularity of mind and foreign language acquisition: a critical reading - Vasconcellos, Maria Lúcia (ALFA: Revista de Linguística, 2001)
In the context of psychological theories assuming an internal structure of mental representations, Fodor (1983) proposes a mandatory informationally encapsulated autonomous processing of specifically linguistic input, maintaining that cognitive skills are neurally localized. He advances the hypothesis of a vertical and modular psychological organization underlying biologically coherent behaviors. This paper offers a critical reading of Fodor's theoretical position in relation to some aspects of Foreign Language Acquisition (FLA), calling into question untenable claims as to information processing, mental representation and perceptual analysis. In view of factors other than grammatical affecting FLA, a strictly modular view of sentence understanding is disputed while a radical connectionist perspective is also found fault with. It is argued that a compromise position might better account for the complex phenomenon of foreign language acquisition.